KEEFEKTIFAN EKSTRAK DAUN PARE (Momordica charantia) DALAM MENGENDALIKAN Crocidokomia pavonana F. PADA TANAMAN SAWI - Hasnah Hasnah; Husni Husni; Nezpi Noza Purnama (Jurnal Floratek, 2013)
The purpose of this study was to obtain effective concentrations of leaf extracts of bitter melon in controlling Crocidolomia pavonana on mustard (Brassia juncea Linn). The experiment was conducted at Laboratory of Plant Pests and Diseases, Faculty of Agricultural Kuala University, Banda Aceh. The study took place from August to November 2010. The experiment was arranged in a Completely Randomized Design (CRD), with six concentration of 0, 5, 10, 15, 20, and 25 ml/L solution. Each treatment was repeated 4 times to obtain 24 units of the experiment. Variables observed were mortality of larvae C. pavonana, formed pupa percentage, emerging imago percentage and feeding deterrent percentage. The results showed that application of leaf extract of M. charatia could control C. pavonana on mustard. The higher concentration of the leaf extract was given, the more effective control was against C. pavonana on mustard plant. The use of leaf extracts M. charantia in concentration of 20% was able to control C. pavonana up to 60%.